Wearing a "self-compassion suit" may offer a performance edge: A qualitative study of serial-winning high-performance coaches - Hägglund, K.; Kenttä, G.; Bentzen, M.; Wagstaff, C. R. D. (The Sport Psychologist, 2025)
High-performance coaches face complex challenges within their profession, which affect both their performance and their well-being. Through a qualitative study design, we aimed to understand how serial-winning high-performance coaches perceive self-compassion practice. Nine Scandinavian participants from various sports (female = 1, male = 8) explored self-compassion through psychoeducation and 1 week of practice followed by interviews. The data were analyzed using reflexive thematic analysis. The three themes are represented via a creative nonfiction story: "We have no fear of self-compassion"; "Realizing why I should be a more compassionate friend to myself, it gives me a performance edge"; and "You have to take the armor off, and that is sometimes hard." This study offers novel insights from serial-winning high-performance coaches—a typically hard-to-reach sample. The findings show how self-compassion was perceived as beneficial based on participants` prolonged experience navigating challenges, and how self-compassion may contribute to psychologically safe high-performance environments.